Photo-induced cation translocation in a molecular shuttle based on a calix[4]-biscrown including DCM and DMABN chromophores. Issue 80 (24th August 2015) - Dozova, Nadia; Kumar, Rajesh; Pradhan, Tuhin; Lacombat, Fabien; Valeur, Bernard; Kim, Jong Seung; Plaza, Pascal
Abstract : A K + ion bound to the DCM-grafted crown of a new ditopic molecular shuttle is shown to be phototranslocated towards the DMABN site. Abstract : We present a new molecular shuttle, consisting of a calixarene core attached to two different photoactive centers, DCM and DMABN. We show that a K + ion bound to the DCM-grafted crown is translocated towards the other site of the molecule upon photoexcitation, but not released to the bulk.